Faktor Prediktor Kepatuhan Clinical Pathways COVID-19 di Rumah Sakit - Musrifatul Uliyah; Abdul Aziz Alimul Hidayat (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Clinical pathways for covid-19 are the best efforts made by nurses in handling cases of covid-19. However, there are still nurses who have not been optimal in implementing COVID-19 clinical pathways. For this reason, this study aims to analyze predictor factors for compliance with Covid-19 clinical pathways in hospitals, Surabaya, Indonesia during the COVID-19 pandemic.Methods: This study used a cross sectional study, with a sample size of 126 nurses selected from a private hospital in Surabaya. Data was collected using the Covid-19 clinical pathways measurement scale instrument and sociodemographic questionnaire, used to obtain information about the characteristics of respondents.Results: The results of statistical analysis with regression test showed p = 0.000, that the predictor factor of clinical pathways adherence was the role of nurses, with a value (OR 379,479, 95% CI 41,391, 3479,165), this shows the role of nurses with good categories will have an impact on high compliance in clinical pathways covid-19, while the factors of age, gender, educational background, and length of work are not predictor factors in the compliance of clinical pathways covid-19 in hospitalsConclusion: Nurses in carrying out their roles well have an impact on Covid-19 clinical pathways compliance, and it is proven that nurses' roles are strong predictors in determining clinical pathways compliance in hospitals. Therefore, the capacity building program and the development of nurse resources are important to be given in order to continue to apply the covid-19 clinical pathways.